Utilização de solvente eutético na carbonização hidrotérmica de resíduo de acerola - Martins, João Paulo Gonçalves (2021)
Hydrothermal carbonization (HTC), in addition to being a convenient method where materials with high humidity and mild conditions of temperature and pressure are used for the pre-treatment of crude biomass and subsequent use as solid fuel, it is a solution for lignocellulosic residues, which are often not used efficiently. The critical point in HTC's process is high pressure. Thus, the use of ionic salts (eutectic solvents) can reduce the system's vapor pressure and improve the properties of hydrochar. Therefore, the objective of this work was to employ the eutectic solvent – choline chloride: urea – in HTC of acerola residue, in order to understand its influence in this process, through the characterization of the main product – solid (hydrochar). The operational conditions of each experimental test were determined using the Central Composite Planning (PCC) with 3 variables: temperature (T), residence time (t) and percentage of eutectic solvent (DES). The response variables considered in this work were the solids yield (SY) and the higher calorific value of hydrocarbons (PCS). The secondary product – liquid (bio-oil) was analyzed by gas chromatography coupled with a mass spectrometer (GC-MS) to identify the compounds. Statistical analysis of the results obtained was performed using analysis of variance (ANOVA) and multiple regression techniques. HTC's multi-response optimization study was performed using the Desirability Function. From the results obtained, it can be said that the system pressure was lower than the pressure of saturated water vapor (conventional HTC) at the respective test temperature. The maximum charcoal yield (68.52%) was obtained under operating conditions of 160 °C – 1.2 h – 60% DES. The highest PCS value was 20.66 MJ/Kg. In this way, the calorific value was improved by a maximum of 10%. The optimal conditions found were T= 160 °C, t= 4 h and DES= 6%. Therefore, it is concluded that the use of this eutectic solvent provided a reduction in the operating pressure, in addition to an improvement in the PCS of the solid.